Optimization Investigation of Biogas Potential of Tithonia Diversifolia as an Alternative Energy Source (International Journal of Chemical and Process Engineering Research, 2016)
This research work dwells on the anaerobic digestions of rumen with Tithonia diversifolia (T. diversifolia) for biogas production. The anaerobic digestions of rumen with T. diversifolia was carried out for 30 days within the mesophilic temperature range (30.0 °C - 40.0 °C) using a digester with dimensions 50 cm x 25 cm. Results obtained indicated that the maximum biogas volume obtained was 7.05 x 10-3 m3 on 29th day. The temperature of the digestate remained constant throughout the fermentation period. The pH of the medium changes progressively from acidic to slightly alkaline (6.41 to 7.2). In order to estimate the statistical analysis, linear regression and correlation model were used, Analysis of Variance (ANOVA) was constructed. The coefficient of determination R2 with Prob>F=0.0001 was 0.7339, the regression parameters βO (intercept) and β1 (slope) were obtained as 6.05 x 10-6 and 1.942 x 10-3, respectively. The Root Mean Square Error (RSME) was 7.84 x 10 -5, the Sum of the Square Error (SSE) was 1.72 x 10-5, the total sum of the square error (SST) was 6.46 x 10-5 and regression of the square (SSR) was 4.74 x 10-6. The estimated regression function equation of biogas volume was expressed as y = 0.00000605239x + 0 .001941651. The physicochemical properties of the digester feedstock before and after the anaerobic digestion showed that the COD, ash content, organic carbon, total kjedahl nitrogen, pH increased after the anaerobic digestion while the total solids, volatile solids, aluminum, copper, iron, calcium and ammonia nitrogen decreased. The C/N ratio of the feedstock was approximately 4:1. The study showed that T. diversifolia with rumen can produce sufficient carbon that accelerated effective gas generation.